HIV Infection Diagnosis in a Late Presenter Patient during a Severe Imported Falciparum Malaria: A Challenging - Pistarà, Eugenia; Marino, Andrea; Ceccarelli, Manuela; Cosentino, Federica; Moscatt, Vittoria; Gussio, Maria; Micali, Cristina; Nunnari, Giuseppe; Cacopardo, Bruno; Celesia, Benedetto Maurizio (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Malaria and HIV share the same epidemiological spreading and coinfection may be clinically challenging. In 2019, nearly all malaria cases reported by EU/EEA countries were imported. Severe falciparum malaria is a medical emergency often associated with poor outcome, even when treated with appropriate therapy. CASE PRESENTATION: Here, we described an unusual case of a late presenter HIV diagnosis made during the management of a severe falciparum malaria in an Italian traveler returning from Nigeria, who did not take antimalaria prophylaxis. Clinical course was complicated by the occurrence of several superinfections caused by deep immunosuppression, and bilateral subsegmental pulmonary embolism. CONCLUSION: Although critical conditions, malaria prompt diagnosis and treatment, along with HIV diagnosis and the successful treatment of occurred superinfection, resulted in a positive outcome.